"Behold the Wicked Abominations That They Do": The Nineteenth-Century Roots of the Evidentiary Approach in American Investigative Journalism. Issue 4 (2nd October 2022) - Lanosga, Gerry
Abstract : The idea of investigative reporting is inextricably intertwined with Watergate in the popular and journalistic imagination. But this article traces the long history of the exposé tradition in American journalism, particularly arguing that the evidentiary mindset of investigative reporters first took root in the ferment of 1830s abolitionism. In myriad pamphlets and newspapers, abolitionists began unearthing and laying before the public documentary proof of the abuses of slavery. The apotheosis of this work came in 1839 with the publication of the book-length American Slavery As It Is: Testimony of a Thousand Witnesses . It was a tour de force of systematic, evidence-based journalism more than a century before the phrase "investigative reporting" came into use. By connecting the idea of exposing hidden wrongdoing with the documentary method, abolition writers established an early legacy of verification as justification for moral outrage in the act of reporting.